Teachers' metacognitive understanding of teaching science in English as a medium of instruction classes - Pun, Jack; Gao, Xuesong (Language awareness, 2024)
Despite the increasing use of English as a medium of instruction (EMI), teachers who teach at EMI schools encounter significant challenges, such as difficulties in teaching content-subjects in English and students' limited understanding of content presented in English. To examine the extent of these challenges, six early-full and 14 late-partial EMI science teachers from eight schools in Hong Kong were invited to participate in semi-structured interviews on the challenges they faced as teachers of EMI science subjects. A biographic approach was used to analyse the interviews, and the results showed that despite the metacognitive overlap between the two groups of teachers, there were noticeable differences in their pedagogical strategies. These findings suggest that the implementation of EMI instruction influences teachers' metacognition and pedagogical practices. Teachers' frequent use of Cantonese (L1) further suggest that English language skills are not as prioritised compared to the subject content. Further research is needed to investigate the complex and diverse factors that influence teachers' metacognition under EMI contexts.